MAINTENANCE OF WEB APPLICATION BASED ON MODEL–VIEW–CONTROLLER ARCHITECTURE (CASE STUDY: HUMAN RESOURCE ASSESSMENT TOOLS) - Dea Rahman Fauzi; Tien Fabrianti Kusumasari; Ekky Novriza Alam (STKIP PGRI Tulungagung, 2025)
One of the causes of project failure in organizations is the mistake of selecting team members who are not suitable. The Website Assessment Tools Application is a web platform that maps employee roles based on individual competencies from various assessment sources. This application was developed to help organizations allocate human resources effectively based on everyone’s competencies. However, the Website Assessment Tools Application has some shortcomings that hinder its functionality, requiring maintenance or improvements to address issues and add new features. This project will focus on the application's functionality, both front-end and back-end. Maintenance will be conducted using the Collaboration Model of Software Development, which consists of five phases, communication/requirement, planning, modeling, construction, and deployment. The results of the Website Assessment Tools Application maintenance will be tested using the Black Box Testing method. The Black Box Testing results show that all scenarios meet the expected outcomes. These results ensure that the Website Assessment Tools Application functions optimally and is ready for organizational use.